2004
DOI: 10.1074/jbc.m402705200
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-3 Binding to the Murine βIL-3 and Human βc Receptors Involves Functional Epitopes Formed by Domains 1 and 4 of Different Protein Chains

Abstract: Interleukin-3 (IL-3) is a cytokine produced by activated T-cells and mast cells that is active on a broadrange of hematopoietic cells and in the nervous system and appears to be important in several chronic inflammatory diseases. In this study, alanine substitutions were used to investigate the role of residues of the human ␤-common (h␤c) receptor and the murine IL-3-specific (␤ IL-3 ) receptor in IL-3 binding. We show that the domain 1 residues, Tyr 15 and Phe 79 , of the h␤c receptor are important for high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 37 publications
5
47
0
Order By: Relevance
“…Previous high resolution structure analyses have shown that the extracellular region of ␤c can exist as a dimer (44,48). In this structure, the ␤c is a homodimer stabilized by domain swapping between domain 1 (D1) of one chain and domain 3 (D3) of the symmetry-related chain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous high resolution structure analyses have shown that the extracellular region of ␤c can exist as a dimer (44,48). In this structure, the ␤c is a homodimer stabilized by domain swapping between domain 1 (D1) of one chain and domain 3 (D3) of the symmetry-related chain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4A). Structural integrity of these mutants was previously verified by measuring their cell surface expression with flow cytometry [23] [24]. The two alanine-mutational variants, sβc(Y18A) and sβc(Y344A), were successfully expressed in Drosophila S2 cells and secreted into the cell culture in amounts roughly equal to that achieved for wild type sβc protein.…”
Section: Mutational Effect On the Il5-il5rα-βc Interactionmentioning
confidence: 99%
“…Tyr18 and Tyr344 of βc (corresponding to Tyr15 and Tyr347 in the crystal structure [25]) have been found to be critical for IL5, IL3 and GM-CSF association into their respective trimolecular complexes [21] [22] [23] [24]. These residues are located in a hypothetical ligand-binding interface of D1 and D4 domains (Fig.…”
Section: Mutational Effect On the Il5-il5rα-βc Interactionmentioning
confidence: 99%
See 2 more Smart Citations